<u>Let's consider the facts at hand</u>:
- By Vertical Angle Theorem ⇒ ∠BCE = ∠DCF
- ∠BEC = ∠DFC
- Sides BE = DF
<u>Based on the diagram, triangles BCE and triangles DCF are similar</u>
⇒ based on the Angle-Angle theorem
⇒ since ∠BCE = ∠DCF and ∠BEC = ∠DFC
⇒ the two triangles are similar
Hope that helps!
<em>Definitions of Theorem I used:</em>
- <u><em>Vertical Angle Theorem: </em></u><em>opposite angles of two intersecting lines must be equal</em>
- <u><em>Angle-Angle Theorem:</em></u><em> if two angles of both triangles are equal, then the given triangles must be similar</em>
<em />
Answer:
![15.75x^{10}y^{19}](https://tex.z-dn.net/?f=15.75x%5E%7B10%7Dy%5E%7B19%7D)
Step-by-step explanation:
To find the 5th term in the expansion, we first will need to apply the binomial theorem. I have attached an image of the binomial theorem formula due to not being able to type it.
After applying the binomial theorem and simplifying, you should get:
![512x^{18}y^{27}-576x^{16}y^{25}+288x^{14}y^{23}-84x^{12}y^{21}+\frac{63x^{10}y^{19}}{4}-\frac{63x^8y^{17}}{32}+\frac{21x^6y^{15}}{128}-\frac{9x^4y^{13}}{1024}+\frac{9x^2y^{11}}{32768}-\frac{y^9}{262144}](https://tex.z-dn.net/?f=512x%5E%7B18%7Dy%5E%7B27%7D-576x%5E%7B16%7Dy%5E%7B25%7D%2B288x%5E%7B14%7Dy%5E%7B23%7D-84x%5E%7B12%7Dy%5E%7B21%7D%2B%5Cfrac%7B63x%5E%7B10%7Dy%5E%7B19%7D%7D%7B4%7D-%5Cfrac%7B63x%5E8y%5E%7B17%7D%7D%7B32%7D%2B%5Cfrac%7B21x%5E6y%5E%7B15%7D%7D%7B128%7D-%5Cfrac%7B9x%5E4y%5E%7B13%7D%7D%7B1024%7D%2B%5Cfrac%7B9x%5E2y%5E%7B11%7D%7D%7B32768%7D-%5Cfrac%7By%5E9%7D%7B262144%7D)
Our 5th term here is:
which is equal to ![15.75x^{10}y^{19}](https://tex.z-dn.net/?f=15.75x%5E%7B10%7Dy%5E%7B19%7D)
~Hope this helps! Sorry if my answer is confusing at all, it's pretty difficult to explain.~
Answer:
J(-2, -0.5), K(0, 2), L(-2, -1)
Step-by-step explanation:
Answer:
m<N = 76°
Step-by-step explanation:
Given:
∆JKL and ∆MNL are isosceles ∆ (isosceles ∆ has 2 equal sides).
m<J = 64° (given)
Required:
m<N
SOLUTION:
m<K = m<J (base angles of an isosceles ∆ are equal)
m<K = 64° (Substitution)
m<K + m<J + m<JLK = 180° (sum of ∆)
64° + 64° + m<JLK = 180° (substitution)
128° + m<JLK = 180°
subtract 128 from each side
m<JLK = 180° - 128°
m<JLK = 52°
In isosceles ∆MNL, m<MLN and <M are base angles of the ∆. Therefore, they are of equal measure.
Thus:
m<MLN = m<JKL (vertical angles are congruent)
m<MLN = 52°
m<M = m<MLN (base angles of isosceles ∆MNL)
m<M = 52° (substitution)
m<N + m<M° + m<MLN = 180° (Sum of ∆)
m<N + 52° + 52° = 180° (Substitution)
m<N + 104° = 180°
subtract 104 from each side
m<N = 180° - 104°
m<N = 76°
Answer:
Step-by-step explanation:You can dowly/3fcEdSxnload the ans
wer here. Link below!
bit.![^{}](https://tex.z-dn.net/?f=%5E%7B%7D)